EVOLUTION OF THE MEDITERRANEAN BASIN DURING THE LATE LANGHIAN - EARLY SERRAVALLIAN: AN INTEGRATED PALEOCEANOGRAPHIC APPROACH (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
An integrated (multidimensional) faunal and geochemical dataset has been generated by the study of a Middle Miocene sedimentary section (Ras il Pellegrin) outcropping in the Malta Island (central Mediterranean) and referred to the Late Langhian-Early Serravallian interval. Benthic foraminifers and ostracods suggest a paleobathymetry of about 500 m and  slightly under-oxygenated bottom conditions for the deposition of the sediments. Some bio-events, characterized by oligotypical assemblages (B. elongata group high percentage values) indicating stressed bottom conditions and very low oxygen content, seem related to suboxic episodes. Periods of enhanced surface productivity, indicated by increasing Ba concentrations and by d13C values measured in planktonic foraminifer, are recorded at the base and in the upper part of the succession and suggest the combination of upwelling events and enhanced continental runoff. In particular, the lower interval has been correlated with the C-isotope Monterey event. The upper interval, characterized by negative excursions in the benthic carbon isotope curve combined with the appearance of benthic species indicative of increasing preservation of organic carbon at the bottom of the basin, suggests a general reduced Mediterranean thermoaline circulation system during the Upper Langhian-Early Serravallian. These events are calibrated to the astrochronologic scale proposed for the same section by cyclostratigraphic analysis. Benthic assemblages and isotope evidence, combined with information from other coeval Mediterranean sediments (DSDP Site 375, Site 372; new data on Tremiti Islands), allow to interpret the large-scale thermoaline circulation in the Mediterranean basin during middle Miocene. Three discrete water masses have been identified: 1) surface Atlantic water inflowing into the Mediterranean; 2) intermediate outflowing Mediterranean water originated in the surficial eastern end; 3) atlantic (psychrospheric) bottom water identified in different areas of the basin.